eCM 2013
DOI: 10.22203/ecm.v026a18
|View full text |Cite
|
Sign up to set email alerts
|

Yield optimisation and molecular characterisation of uncultured CD271+ mesenchymal stem cells in the reamer irrigator aspirator waste bag

Abstract: Bone reconstruction requires the use of autografts from patients' iliac crest (IC); for large-volume defects bone void fillers and autologous mesenchymal stem cells (MSCs) are often added. The Reamer/Irrigator/Aspirator (RIA) device provides the means of harvesting large amounts of autograft and additionally yields a waste bag containing MSCs, which is currently discarded. The aim of this study was to enumerate and characterise native MSCs from RIA waste bag and compare them to 'gold-standard' donormatched MSC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 42 publications
3
15
0
1
Order By: Relevance
“…MSCs identified by negative to low expression of CD45 and positive expression of CD271 (CD45 −/low CD271 + ) [16,32,34], as well as cells with positive expression of CD45 and low expression of CD271 (CD45 + CD271 low ) were examined in detail. Expression of a range of cell surface markers was examined by incubation with monoclonal antibodies; CD3, CD14, CD19, CD31, CD34, CD73, CD90, CD105, CD146, CD235a, mesenchymal stem cell antigen 1 (MSCA-1) and sushi domain containing 2 (SUSD2) [23,38,39] (Table 1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…MSCs identified by negative to low expression of CD45 and positive expression of CD271 (CD45 −/low CD271 + ) [16,32,34], as well as cells with positive expression of CD45 and low expression of CD271 (CD45 + CD271 low ) were examined in detail. Expression of a range of cell surface markers was examined by incubation with monoclonal antibodies; CD3, CD14, CD19, CD31, CD34, CD73, CD90, CD105, CD146, CD235a, mesenchymal stem cell antigen 1 (MSCA-1) and sushi domain containing 2 (SUSD2) [23,38,39] (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…TaqMan gene expression assays were then used according to the manufacturer’s instructions to measure transcript expression of genes important for bone regeneration. These were bone morphogenic protein 2 (BMP-2) an essential mediator of fracture healing [42], vascular endothelial growth factor C (VEGFC) an important stimulator of angiogenesis [43], Collagen type I alpha 2 (COL1A2) and osteonectin (SPARC) two factors involved in matrix deposition and mineralisation [34] and Stromal derived factor 1 (CXCL12) a chemokine capable of influencing chemotaxis of a wide range of cell types including MSCs [44,45]. Transcript expression was measured relative to the housekeeping gene hypoxanthine-guanine phosphoribosyltransferase (HPRT) in three matched samples, Pre and Post enrichment, from each tissue.…”
Section: Methodsmentioning
confidence: 99%
“…Previous reports have shown that LNGFR is involved in cell death and axonal degeneration in response to injury . Increasing numbers of studies have demonstrated that LNGFR can serve as a cell surface marker for mesenchymal stem cells (MSCs) and that LNGFR‐positive MSCs present increased potential for osteogenesis . In this study, EMSCs were isolated from embryonic facial processes and sorted to obtain LNGFR + EMSCs and LNGFR − EMSCs.…”
Section: Introductionmentioning
confidence: 99%
“…12 Increasing numbers of studies have demonstrated that LNGFR can serve as a cell surface marker for mesenchymal stem cells (MSCs) and that LNGFR-positive MSCs present increased potential for osteogenesis. [13][14][15][16][17][18] In this study, EMSCs were isolated from embryonic facial processes and sorted to obtain LNGFR + EMSCs and LNGFR − EMSCs. We further demonstrated that LNGFR + EMSCs had a higher osteogenic capacity and lower SOST levels compared with LNGFR − EMSCs and that SOST negatively regulated the osteogenic differentiation of EMSCs.…”
Section: Introductionmentioning
confidence: 99%
“…30 CD61, or integrin beta-3, is believed to be negative in MSCs. 31 CD90 (thymocyte differentiation antigen-1,Thy-1) is a positive marker recommended by the International Society for Cellular Therapy position statement. 24 CD106 (vascular cell adhesion molecule 1, VCAM-1) is expressed on activated endothelial cells, and it facilitates adhesion of haematopoietic cells to endothelial cells and subsequently their migration into tissue.…”
Section: Methodsmentioning
confidence: 99%